Inhibitory effects of 19 antiprotozoal drugs and antibiotics on Babesia microti infection in BALB/c mice - Jun-ming Yao; Hao-bing Zhang; Cong-shan Liu; Yi Tao; Meng Yin (Journal of Infection in Developing Countries)
Introduction: Different results have been achieved in the evaluation of antiparasitic drug activity in Mongolian jirds, hamsters, and BALB/c mice infected with Babesia microti. The aims of the present study were to find a preferable method for drug screening and to re-evaluate the activity of several drugs against B. microti. Methodology: The activity of 19 drugs on B. microti-infected BALB/c mice was evaluated. The study was built on Peters' four-day suppressive test, and the pathogenicity of the blood from the treated mice was also used as indicator. Results: The results showed that 15 of the 19 drugs had little or no in vivo effect against B. microti. The inhibitory rates of atovaquone and azithromycin were high at all doses, but the microscopy-negative blood of recovered mice was still infectious. Similar to robenidine hydrochloride at 25 and 50 mg/kg, primaquine at 100 mg/kg had a 100% inhibitory rate. Robenidine hydrochloride achieved a 100% inhibitory rate at 100 mg/kg, and the blood of recovered mice did not result in parasitemia in subpassage experiments. Parasite-negative blood from mice treated with antimalarial drugs (clinically used for babesiosis) still caused parasitemia in subpassage experiments. This suggests that these drugs cannot eradicate the parasites. Conclusions: Peters' four-day suppressive test and the pathogenicity of the blood from the treated mice are suitable methods for preliminary investigating possible drugs against B. microti. Considering that robenidine hydrochloride achieved the best activity against B. microti in BALB/c mice in our study, further studies are needed.